DESIGN OF AN EDUCATIONAL GAME SORTING WASTE ANDROID BASED - Nyoman Ayu Gita Gayatri (Universitas Multimedia Nusantara, 2023)
Educational game is a learning media that is educating, where the media can encourage students to think creatively and carry out activities with fellow students in playing games in learning activities. Educational games are very interesting to develop, there are several advantages of educational games compared to conventional educational methods, one of the main advantages of educational games is the visualization of real problems. Based on the pattern belongs by the game, players are required to learn so they can solve existing problems. With these developments, it can be used as children's learning to introduce waste, which many still do not understand in terms of sorting organic and non-organic waste. environment and add value to the waste itself. The current waste problem is getting more and more unavoidable. It will be more complex if it continues to be left unchecked. The education carried out starts from early childhood with the aim of instilling a pattern of cleanliness and discipline in disposing of waste. This educational game based on Android is supported by smartphone technology that is growing rapidly. This game can be used as an alternative medium of learning in Early Childhood Education in changing conventional learning methods into learning simulation games, so as to develop the children's creativity, because educational games have elements of challenge, accuracy, reasoning and ethics. Currently, smartphones are also equipped with many new facilities that allow users to do many things. Smartphones have also been equipped with operating systems such as Android. Android is an operating system for Linux-based Mobile devices that includes an operating system, middleware, and applications. Android provides an open platform for developers to create their own applications for use by various mobile devices. Keyword : Educational games, waste, Early Childhood Education